Diameter dependent optical and field emission properties of vanadium pentoxide nanobelts. Issue 10 (July 2020) - Firdous, Mashal; Butt, Faheem K.; Zaman, Sher; Ahmad, Junaid; Hassan Farooq, Masood Ul; Safdar, Muhammad; Hussain, Saghir; Zapata, Maximiliano J.M.; Maqsood, Hafsa; Cao, Chuanbao
Abstract: Vanadium Pentoxide is considered as an intriguing material for several advanced technological applications such as supercapacitors, Lithium-ion batteries, photo-catalysis and optical waveguide. In this work, we have presented a facile and non-toxic method for the synthesis of Vanadium Pentoxide nanobelts. Considering the aforesaid motivations, we tuned the size of Vanadium Pentoxide nanobelts by simply varying the synthesis temperature. The XRD results confirm that the obtained phase is Vanadium Pentoxide with no impurities found within the experimental limitations. The analysis by Scanning Electron Microscopy (SEM) depicts that the diameter of nanobelts decreased from 52.7nm to 44.7nm with the increase in synthesis temperature within range 180 o C-220 °C respectively. The UV–Vis-Spectrum shows that bandgap of nanobelts increased in the range 2.25eV-3eV with the increase in synthesis temperature within range 180 o C-220 °C. For field emission measurements, the variation in field enhancement factor and turn-on voltage is also observed. These results indicate that by just varying a simple parameter one can tune the band gap and electronic properties of Vanadium Pentoxide nanobelts. These studies show that Vanadium Pentoxide nanobelts can be promising candidate for optoelectronic device.